A Note on COVID-19 and the ‘Drop of Honey Effect’ – Risk Management in a Strong Uncertainty Environment - Filipe, J. (International Journal of Finance, Insurance and Risk Management, 2022)
Purpose: Covid-19 is a pandemic disease that spread all over the world, provoking disruption in health, social, economic, financial systems. We propose the ‘drop of honey effect’ metaphor to show the implications the spread of the virus had in the national systems and in the international order. Design/methodology/approach: We use chaos theory framework and the ‘drop of honey effect’ metaphor to show how fast the disease spread and the consequences it has. Findings: A disease that appeared in a specific region, rapidly spread for the world with huge consequences at social, economic, financial dimensions. New uncertainty environments of crisis demand new tools and approaches.